La dynamique du décrochage local des élèves en classe structurée par un faisceau de préoccupations « travail - jeu » - Olivier Vors (Université de Provence, 2016)
This research considers the dropout as a process, from a personal course and having its own dynamics finding its origins within the classroom by misbehavior. The purpose of our study is to understand the dynamics of local drop-out by analyzing the activity of students during physical education class in middle schools belonging to the compensatory policy. The theoretical and methodological framework used is the "course of action" (Theureau, 2006). The local dropout of school work is analyzed in terms of student engagement in the lesson according to their concerns bifurcations. Eleven students from 6th and 5th in middle schools were studied in a gymnastics workshops. The collection of data is made from video recordings and interviews of self-confrontation. Data processing aimed to analyze the activity of the students and in particular their concerns, perceptions and knowledge used in action. The results show that the activity of the students is organized by two concerns "work - play" including its own dynamic alternating phases of drop-out and of hang up the school work.